2017
DOI: 10.1177/1179299x16684640
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer deaths worldwide. The HCC diagnosis is usually achieved by biomarkers, which can also help in prognosis prediction. Furthermore, it might represent certain therapeutic interventions through some combinations of biomarkers. Here, we review on our current understanding of HCC biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 89 publications
0
110
0
2
Order By: Relevance
“…In similar studies, some novel biomarkers were also proposed for Early-stage HCC diagnosis and differentiate AFPnegative Early-stage HCC from LC [46]. Fucosylated Paraoxonase 1 (Fuc-Pon1) was proposed as a promising biomarker for diagnosis of early-stage HCC and distinguishing AFP-negative early-stage HCC from LC patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies, some novel biomarkers were also proposed for Early-stage HCC diagnosis and differentiate AFPnegative Early-stage HCC from LC [46]. Fucosylated Paraoxonase 1 (Fuc-Pon1) was proposed as a promising biomarker for diagnosis of early-stage HCC and distinguishing AFP-negative early-stage HCC from LC patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…But, AFP testing lacks sensitivity and specificity for effective surveillance with limited diagnostic accuracy in detecting small HCC and mainly restricted to those areas endemic with HBV. [73][74][75][76] AFP-L3: It is an isoform of AFP. It is used as an early biomarker of HCC when the tumor size is around 2 cm.…”
Section: Genomic Variants Associated With Hcc: Systems Biology Challementioning
confidence: 99%
“…As the size of tumor increases, the sensitivity of this marker is increased. 73,74,76 APO-J: APO-J/Clusterin is a glycoprotein with seven glycosylated sites. It is more sensitive and specific when compared to AFP.…”
Section: Genomic Variants Associated With Hcc: Systems Biology Challementioning
confidence: 99%
“…AFP is the most widely used tumor biomarker currently available for early detection of HCC, and the widely accepted threshold of serum AFP is 20 ng/mL. It has been reported that at this threshold, serum AFP had a sensitivity of 41-65% and specificity of 80-94% 36 . We grouped the 19 HCC patients in our cohort into two groups, according to an AFP-cutoff of 20 ng/mL (Table 1), computed the fold change of protein expression between tumorous and non-tumorous tissues, and checked the protein regulation pattern of 11 patients with high AFP level (> 20 ng/ml) and six patients with low AFP level (< 20 ng/ml), respectively.…”
Section: Proteins With Altered Abundance In Hcc Patients With High Sementioning
confidence: 99%